Comparison between fourier and corrected fourier series methods - Zainal, Nor Hafizah; Kilicman, Adem (Universiti Putra Malaysia Press, 2013)
Fourier series is a method that can solve for many problems especially for solving various differential equations of interest in science and engineering. However, Gibbs oscillations will be occurs when using a truncated Fourier series. Thus, we solve the problems by using the corrected Fourier series. Here, we want to compare the results between the solutions that we get from Fourier series method and Corrected Fourier series method. The comparison between these two methods will be our finding.